THE EFFECT OF ANIMATED FILM ON STUDENTS’ ABILITY TO WRITE NARRATIVE TEXT AT CLASS X MIA 5 OF SMAN 9 KENDARI - Wahyuni, Sri (Journal of Teaching of English, 2019)
Who registers in academic year 2014/2015. This research involved 40 students at class X. The instrument of this study was writing task in narrative genre. And the criteria of students‟ writing were assessed from five aspects of writing, namely content, organization, vocabulary, language use, and mechanic. The data were obtained by using two essay writing tests. They were pre-test and post-test. The pre-test was given before the treatment and the post-test was given after the treatment finished. The data of the pre-test and post-test were analyzed by means of descriptive and inferential statistics. After the data were tested and found to be normal, the hypothesis was tested using the analysis of paired sample test. The result showed that there was significant effect of students‟ writing ability after teaching by using audio visual media (animated film). It can be seen on the result of the hypothesis testing using  paired sample test. The mean score of pre-test was 61.92 and mean score post-test was 75.63. Morever, as a  result the probability value of .000 (p value) was less than the level of significant (p < .05). Therefore, it can be said that using audio visual media (animated film) gives significant effect to increase students‟  ability to write narrative text at class X Mia 5 of SMAN 9 Kendari. Keywords: Writing, Animated Film, Narrative Text